Assessment of the Potential of Gambling Tourism as a Restarting Factor for The Development of Tourist Destination of Greater Sochi (Laisvalaikio tyrimai, 2018)
Research background. Currently, gambling tourism is one of the most popular forms of leisure all across the globe. It is apparent that, when a business as lucrative as gambling has something to do with the development of tourism, its impact on a tourist destination, both current and future, can be impressive. Research into this type of tourism reveals an interrelationship between gambling tourism and certain socialeconomic variables in the development of tourist destinations – the gambling business can be a crucial component in the attractiveness of tourist destinations and facilitate economic stability and prosperity in the area. The development of gambling tourism is regarded as a restarting and renewing factor for the development of tourism destinations which can potentially facilitate their development through the reinvestment of revenue into their economic and political culture. Issues in the development of tourist destinations and gambling tourism have been examined in works by W. M. Abbott, A. A. Volberg (2006), А. Alegria (2014), L. Caneday, J. Zeiger (1991), M. C. Hall (2008), R. Harrill (2003), S. K. Kang, C. K. Leeb, Y. Yoonb, P. T. Long (2008), T. K. Lee, C. K. Lee (2014), A. A. Ligthelm (2009) and others. Research aims. The study aims to assess the potential of gambling tourism as a factor in the development of tourist destinations through the example of Greater Sochi. Inferences. The development of a tourist destination requires forming some kind of supply, with the process of planning and development of gambling tourism approached based on integrated analysis, including by the local community. Taking into account the foreign experience of sustainable development of tourist destinations via the economic and social effects of gambling tourism, this impact ought to be assessed using a model for establishing a balance between revenue and expenditure. The tourist destination of the city of Sochi as a tourism product is unique, with its peculiarities, various attractions, its original environment, culture, and history. Researchers, who generally have been positive in their assessments of the economic effect from creating a gambling zone, have also been stressing the need to use this tool judiciously and competently. The assessment of Sochi by representatives of its business community and public as a gambling tourist destination is mixed. At the moment, the prospects of a gambling zone in Sochi are quite undecided, as no site has been determined for the zone, there is a lack of investors willing to do it, and there is no developed concept for the formation and development of a gambling zone in Sochi. Gambling tourism could produce a positive impact, since it could attract well-off tourists during the off-peak season. Immune to seasonality, it could ensure tourism flows all year round. Gambling tours, as a component in the destination’s tourism product, could help diversify and improve tourism products and services, which would help attract new tourists and foster a new image for the destination, with a view to boosting its competitiveness.Keywords: leisure, gambling tourism, destination, gambling business, city of Sochi.